(untitled) (Bulletin KNOB, 2003)
Huis Henegouwen, later called Fortuijn, gave its name to the street on which it is situated, one of the most important business streets of Bergen op Zoom. The house was burnt down in the fire of 1397, but wall material has been reused, as brick formats and burning marks show. The author examines the type of ownership of the adjoining premises, property and alleys. The present premises consist of a medieval front and back part of the house with a partially built-over open hallway on the south side of it. Lamp niches in the cellar walls of the back part of the house and two spacious storage niches on both sides of a chimney flue on the ground floor of the back part of the house against the northern wall also belong to the oldest building phase. After the fire the still existing sleeper beams and secondary beams were put in, just as the dendrochronologically dated roof from 1404. The wall posts and curved braces supporting the sleeper beams have disappeared, but a profiled soleplate is still present. The wood construction of the back part of the house was completely renovated around 1600, but the oak roof is medieval. In 1893 an extensive refurbishment took place, involving a new facade, stucco ceilings and decorative painting on the floorboards of the back part of the house (1st floor). Initially, a brewery was established here, and more recently an association building and a hotel, which latter function the house has had ever since the recent restoration. In this restoration the historical constructions were restored as much as possible and made visible.